Species of Candida in Oral Cavity in Underfed Children: A Case of Candida dubliniesis - Mireya Mendoza; Ana Brito; Elvia Díaz; Rosana Ramos (Kasmera, 2006)
In this study the incidence of the species of Candida in the healthy oral cavities of an infantile population suffering from malnutrition was studied. Diverse species of Candida were described, C. albicans was isolated from 29.4%, one was subsequently identified as C. dubliniensis by PCR using specific primers for this species.